The business cycle in postwar Lebanon - Dibeh, Ghassan (2008)
The postwar business cycle in Lebanon was dominated by the exchange rate based stabilization (ERBS) program implemented by the successive postwar governments. In the early period 1993–2002, a boom-bust dynamics was generated during which the economy exhibited the well-documented stylised facts of ERBS programs. The paper develops a cyclical index (ci) for Lebanon during this period and a VAR model shows that real interest rates (rr) had a significant impact on the dynamics of the business cycle during the early ERBS period. The second period 2002–2005 was marked by a recovery generated by foreign aid given to Lebanon in the Paris II international donors' conference held in November 2002. The period ended in a recession in 2005 brought about by the assassination of Lebanon's ex-prime minister Rafic Hariri. The third phase of the business cycle was caused by the Israel–Lebanon war in the summer of 2006 which led to widespread civilian and infrastructure damage and ended a brief recovery in early 2006. Throughout the period 2002–2006, foreign aid was instrumental in the resilience of the ERBS program.